Incidence and Risk Factors of Infection After Fracture Fixation: A Multicenter Cohort Study - Baisheng Wang; Jingdong Zhang; Wenfeng Han; Xin Tang; Feng Tian (Orthopaedic Surgery)
ABSTRACT Purpose Infection after fracture fixation (IAFF) is a severe complication. There are few multicenter studies targeting IAFF. This paper identifies independent risk factors associated with IAFF by analyzing multicenter clinical data. Appropriate interventions should be implemented to reduce the risk of IAFF. Methods This is a multicenter retrospective cohort study. This study screened medical records of patients who underwent internal fixation for fractures at participating medical institutions from January 1, 2011, to December 31, 2020. Data extraction included demographic characteristics, disease features, surgical variables, and laboratory indicators. Logistic regression analysis was employed to identify the relationship between relevant risk factors and IAFF. Research data were sourced from the hospital's electronic medical record system and self‐constructed databases. Results In our study, 202 patients who underwent internal fixation for fractures experienced postoperative infections, which corresponds to an overall incidence rate of approximately 1.7%. The predominant pathogen identified in these infections was Staphylococcus aureus. A multifactorial analysis indicated that several factors were independently associated with the occurrence of IAFF. These factors included BMI ranges of 24.0–27.9 and 28.0–31.9, smoking, a high ASA score, high‐energy trauma, diabetes, open fracture, seasonal timing of the surgery (summer), bone grafting, drainage duration, surgical duration ≥ 180 min, and A/G ratio < 1.2. Conclusions We strongly recommend that orthopedic surgeons perform comprehensive preoperative assessments on fracture patients to identify factors that may increase the risk of infection. Through the implementation of targeted interventions and beneficial modifications to these modifiable risk factors, it is possible to lower the incidence of IAFF. Additionally, proactive screening, risk stratification, and thorough patient education should be prioritized for patients with high risk but nonmodifiable factors.